Pengaruh Harga Komoditas Dunia Terhadap Indeks Harga Saham Gabungan (IHSG) Di Bursa Efek Indonesia Dengan Menggunakan Vector Error Correction Model (VECM) - Ahmad Ernanda Dwi Saputra; Giriati Giriati; Anggraini Syahputri; Wendy Wendy; Anwar Azazi (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to analyze whether global commodity prices, namely palm oil, gold, and crude oil, affect the Jakarta Composite Index (JCI) on the Indonesia Stock Exchange during the 2020–2024 period, focusing on short-term and long-term impacts through the Vector Error Correction Model (VECM). Based on the analysis, it is concluded that the three commodities have different influence patterns. Palm oil prices have a significant negative impact on the JCI in both the short and long term. Gold prices have a significant positive impact in both time frames. Meanwhile, crude oil prices only show a significant positive impact in the short term, and an insignificant impact in the long term. VECM estimation supports the understanding of transmission mechanisms in an open economy. Global commodity price shocks do not directly affect the domestic stock market permanently, but rather through different adjustment processes between commodities. The variation between short-term and long-term impacts confirms that each commodity has a unique role, level of influence, and duration of impact on the JCI movement.